2012
DOI: 10.1039/c2cc36712b
|View full text |Cite
|
Sign up to set email alerts
|

“Click” polymerization on a self-assembled monolayer: a convenient approach to functionalize various surfaces with polytriazoles

Abstract: "Click" polymerization reaction has been performed on the functional self-assembled monolayer to incorporate polytriazoles. Ellipsometric and atomic force microscopic studies indicated a high degree of polymerization and fairly dense surface coverage. Band gap calculation revealed the possibility of its use as a semiconducting material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…The Figure 12 present the UV-Vis spectra of the synthesized polymers realized in DMF, these results show the existence of an intense peak at 270 nm attributed for the transition (π → π *), the polymer (H) present a second transition (n → π *) observed at 310nm, this transition was absent in the other polymers because their solubility in DMF was low. Results of UV-Vis spectroscopy are consistent with those found by Samanta et al [19], which proves that synthesized polymers may fall in the category of semiconductors.…”
Section: [4-{(1s3r5r7r)-57-dihydroxy-22-dimethylhexahy Dro-13-bsupporting
confidence: 90%
“…The Figure 12 present the UV-Vis spectra of the synthesized polymers realized in DMF, these results show the existence of an intense peak at 270 nm attributed for the transition (π → π *), the polymer (H) present a second transition (n → π *) observed at 310nm, this transition was absent in the other polymers because their solubility in DMF was low. Results of UV-Vis spectroscopy are consistent with those found by Samanta et al [19], which proves that synthesized polymers may fall in the category of semiconductors.…”
Section: [4-{(1s3r5r7r)-57-dihydroxy-22-dimethylhexahy Dro-13-bsupporting
confidence: 90%
“…To the best of our knowledge, there is hardly any report to employ fullerenes directly in "click" polymerization to obtain polytriazoles with multiple fullerene units containing thiophenes. Only recently we reported that thiophene-based polytriazoles [13] and polyacetylenes [14] could be synthesized on flat surfaces using a graft through approach on self-assembled monolayer (SAM) [15,16]. However, the studies were focussed on flat surfaces which were distinctly different from curved surfaces like fullerenes.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Due to the optical transparent nature and the property of high electrical conductance, ITO acts as the most preferable anode in organic electronic equipment and planar heterojunction perovskite solar cell. [ 111–113 ] In a recent review, we discussed methods of immobilization of conjugated and semiconjugated organic small molecules/polymers anchored on functionality decorated surfaces by different surface grafting techniques and their applications are solar cell and biotechnology. [ 114 ] Apart from various conductive substrates, Pisoni et al.…”
Section: Perovskite Solar Cellmentioning
confidence: 99%